Pola Komunikasi Suami Istri Dalam Penyelesaian Masalah Di Awal Masa Pernikahan - Evi Enitari Napitupulu; Rachel Mia Lorenza Lumban Toruan; Monika Simanjuntak (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
The background of this research is the communication patterns of husband and wife conflict resolution in early marriage. The phenomenon that is of concern is how to resolve conflicts that befall newly married couples which often cause divorce at a relatively young age of marriage. The purpose of this study was to determine openness, empathy, supportive attitude, positivity, equality, communication patterns in resolving marital conflict in the early days of marriage. The research method in this study is descriptive qualitative and life history. Data obtained through in-depth interviews, observation, and literature. The informants interviewed were seven families. Data analysis uses the Miles and Huberman models. The results of this study indicate that some husband and wife are open and do not find it difficult to be open to their partners in discussing the conflicts that occur. However, some husbands and wives find it difficult to open up to their partners because they are worried that the problems will become more complicated if they open up to their partners. In this study, all married couples showed a sense of empathy for their partners so that this could show that their partners wanted to understand and accept the problems that occurred. The existence of a supportive attitude given by husband and wife to their partners can make household problems resolved quickly. The support needed by husband and wife can be in the form of verbal, non-verbal and material support. Positive attitudes in conflict resolution carried out by married couples in this study are willing to give in to their partners and surrender to the problems that occur.